2017
DOI: 10.5897/jssem2015.0566
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wood charcoal from Chlorophera excelsa on soil properties and yield components of maize

Abstract: Wood charcoals were mainly used for smoking of fish, meat and frying of corns and many times dump off as wastes in southeast, Nigeria. Their nutrient recycles and release when used as soil amendment has not been considered and evaluated by farmers in the southeast, Nigeria. This study was therefore carried out to assess the efficiency of wood charcoal technology in improving soil productivity. Influence of wood charcoal from Chlorophera excelsa on soil properties and yield components of maize were evaluated. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This pattern is reported by other countries in Africa. For instance, Nweke (2017) reported that, a large quantity of wastes from wood charcoal was dumped off as wastes in many parts of Nigeria. The results show that the main two preferred techniques for reducing pollution caused by charcoal wastes in the area were throwing onto an open areas and pit holes dug near backyards.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern is reported by other countries in Africa. For instance, Nweke (2017) reported that, a large quantity of wastes from wood charcoal was dumped off as wastes in many parts of Nigeria. The results show that the main two preferred techniques for reducing pollution caused by charcoal wastes in the area were throwing onto an open areas and pit holes dug near backyards.…”
Section: Resultsmentioning
confidence: 99%
“…While soils around kiln sites were found to have high infiltration rates, they had reduced overland flow and less erosion. Elsewhere, Nweke (2017) in South east Nigeria and Deenik et al (2011) in Hawaii show that, increasing use of wood charcoal wastes on soils had improved the soil properties by increasing soil pH level by about 1.5 units compared with soils that have not been mixed with charcoal. The increase in pH had positive impact on soil-plant nutrients and eventually on crop yields.…”
Section: Treatment Of Wood Charcoal Wastes For Environmental Healthmentioning
confidence: 99%
“…In this case test is valuable; the top 6cm-9cm soil should be sampled for nitrates. Other important tests might include testing for soluble salts, cation exchange capacity (CEC), calcium, magnesium, sulphur and trace elements known to be problem in the area (Barber et al, 1961, Scott and Hanway, 1960, Hanway et al, 1962, Edward 1992, ETC 2008Zhang et al, 2004;Nweke 2017). According to Brady and Weil (1999) it is advisable to send the sampled soils to laboratory located in the same region or location from which the soils are sampled (collected) they may have access to data correlating analytical results to plants responses on soils similar nature.…”
Section: Chemical Analysis Of Soil (Soil Testing)mentioning
confidence: 99%
“…Studies (Antal and Grønli 2003;Ishengoma et al 2016;Nweke 2017) report that waste charcoal such as tree barks, residues, and specks of dust are generated mainly due to the low efficiency of locally-made earth kilns during the carbonization process (Figure 1A), means used in the transportation, handling in the warehouses, and handling in the marketing or collection centers. Despite the potential of wood waste charcoal as recycled fuel energy, animal feed supplement Louis et al (2018), and green manure, waste charcoal is considered useless in many low-income countries and thus disposed off with little or no consideration of its impact on the environment.…”
Section: Introductionmentioning
confidence: 99%